Politeness Strategies Used in Kamala Harris’s and Donald Trump’s 2024 Post-Election Speeches - Silitonga, Mega Uli Arta; Rangkuti, Rahmadsyah (JALL (Journal of Applied Linguistics and Literacy), 2025)
After the election results were announced, to maintain a personal face and respect the face of the audience, Kamala Harris and Donald Trump performed their post-election speeches on November 6th, 2024. This study focused on politeness strategies used by Kamala Harris to handle her defeat and by Donald Trump to achieve his victory. This study used a qualitative approach with a content analysis design to analyse and discuss the use of politeness strategies in Harris’s and Trump’s post-election speeches using the politeness strategies framework of Brown and Levinson (1987). The data were collected from the YouTube platform. The data showed that Harris’s and Trump’s speeches used different politeness strategies. According to this study, Kamala Harris was the only speaker to employ all four of the main politeness strategies, while trump only used 2 main strategies. However, the usage of positive politeness: including the speaker and the hearer in the activity, was the first dominant strategy between both candidates. In the context of gender, Harris used feminine politeness and tended to perform collaborative strategies, whereas Trump mostly employed demands and exaggerating, which he performed as masculine politeness.